The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ma16020661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Dry Sliding Wear Behavior of the Mg-3Zn-0.4Ca Alloy for Biodegradable Implants

Abstract: The wear behavior of the Mg-3wt.% Zn-0.4wt.% Ca (ZX30) alloy was tested using a pin-on-disc configuration with AZ31 alloy discs as counterparts under dry sliding conditions. The ZX30 alloy was tested in different states: as-cast, solution-treated, peak-aged, and over-aged. Wear rates and friction coefficients were measured at different loads and sliding speeds. Abrasion and oxidation were the main wear mechanisms found in all the conditions tested. Moreover, aluminum oxides were detected on the worn surfaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The Ca element will nucleate and precipitate on grain boundaries, which inhibit the growth of grains and play the role of grain refinement. At the same time, the Mg 2 Ca phase with good thermal stability is formed when an appropriate amount of Ca is added to the Mg alloy, which can hinder the grain boundaries slip at higher temperature and improve the creep resistance of the alloy [ 11 , 12 ]. It was found that the Mg-Ca alloy has excellent corrosion resistance, high temperature creep performance, and high temperature mechanical properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ca element will nucleate and precipitate on grain boundaries, which inhibit the growth of grains and play the role of grain refinement. At the same time, the Mg 2 Ca phase with good thermal stability is formed when an appropriate amount of Ca is added to the Mg alloy, which can hinder the grain boundaries slip at higher temperature and improve the creep resistance of the alloy [ 11 , 12 ]. It was found that the Mg-Ca alloy has excellent corrosion resistance, high temperature creep performance, and high temperature mechanical properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%